Soci-economic factors affecting implementation of community-managed tsetse control in Busia District, Kenya. - Mwangi, D.K. (University of Reading, 1996)
A study was conducted in six villages of Busia District Kenya, to assess the socio-economic factors affecting implementation of a community-managed tsetse control programme. The study design had three Phases: planning (Phase 1), implementation (Phase 2) and monitoring and evaluation (Phase 3). Only the planning and implementation Phase are discussed in this thesis. The main objective of Phase 1 was to assess the willingness of the community to get involved in tsetse control. Data were collected at the levels of the community and the individual households. A combination of qualitative (key informant interviews, focus groups and community profiling exercises) and quantitative methods (household survey) were used. A contingent valuation technique was used during the survey to assess people's willingness to contribute resources in support of tsetse control. Results of focus groups indicated that most people related tsetse fly and the disease. However, the frequent mention of witchcraft and other supernatural phenomena suggested that people did not completely believe in a scientific explanation. Community education on issues related to the disease and tsetse control and the importance of community participation was achieved through poster presentation and social drama. Results of the survey conducted with a random selection of 180 heads of households showed that 95% were willing to contribute money and/or labour towards tsetse control. The variables influencing willingness to contribute money were the level of formal education and experience with bovine trypanosomiasis. Those influencing willingness to contribute labour included education level, and information on implications of tsetse control. Results of Phase I were used to design Phase II. Two villages were selected to receive assistance in implementing a pilot study on tsetse control using traps owned by the community. The main objective was to study community approach in implementation process and to assess the validity of contingent valuation technique in estimating people's willingness to participate.